2019
DOI: 10.24875/bmhim.m18000016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de placa dentobacteriana y caries dental en el primer molar permanente en una población escolar del sur de la Ciudad de México

Abstract: Tooth decay develops rapidly in the first permanent molars; however, it does not receive the necessary care because it is usually unknown that it is a permanent tooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
2
0
8
Order By: Relevance
“…In patients with accompanied orthodontic problems, it is difficult to make correct recommendations and make evidencebased decisions about prognosis, and long-term vision is essential when planning. 3 Within the limits of this study, it has been observed that ideal spontaneous space closure and ideal occlusion can be achieved, although it was extracted in the late period. In ideal occlusion, rotation or tipping after extraction in a late period; permanent third molar presence and eruption pressure were more effective than the eruption direction and angle of the PSM tooth.…”
Section: Discussionmentioning
confidence: 72%
“…In patients with accompanied orthodontic problems, it is difficult to make correct recommendations and make evidencebased decisions about prognosis, and long-term vision is essential when planning. 3 Within the limits of this study, it has been observed that ideal spontaneous space closure and ideal occlusion can be achieved, although it was extracted in the late period. In ideal occlusion, rotation or tipping after extraction in a late period; permanent third molar presence and eruption pressure were more effective than the eruption direction and angle of the PSM tooth.…”
Section: Discussionmentioning
confidence: 72%
“…La valoración clínica de gingivitis se realizó con base en la categoría de presencia o ausencia clínica de la inflamación de la encía, también se utilizó el índice de Massler y Schonn que valora tres zonas vestibulares de la encía: la papilar, la marginal y la adherida, a fin de determinar las zonas de la encía con inflamación. Cuando ninguna de las zonas presentó signos patológicos al diente, se lee en (Taboada & Talavera, 2011):…”
Section: Resultsunclassified
“…El pico de severidad es independiente en ambos sexos, influenciado por el incremento en los niveles de hormonas sexuales sobre la fisiología de los tejidos periodontales y la colonización del periodonto por bacterias. Se ha reportado una incidencia del "90% al 100% en adolescentes, en adolescentes escolares de Estados Unidos una prevalencia de gingivitis del 60% resultando más afectadas las áreas molares en el maxilar superior y los incisivos centrales en la mandíbula" (Taboada & Talavera, 2011).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…[5] In Mexico, dental caries is a public health problem that is present in preschoolers and school children; it is highly prevalent and considered to be the main cause of premature dental loss during childhood. [68]…”
Section: Introductionmentioning
confidence: 99%